2018
DOI: 10.2147/copd.s166023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tiotropium/olodaterol on lung volume, exercise capacity, and physical activity

Abstract: PurposeThis study evaluated the efficacy of tiotropium/olodaterol vs tiotropium on lung function, exercise capacity, and physical activity in patients with COPD.Patients and methodsA total of 184 patients aged ≥40 years with COPD (Global Initiative for Chronic Obstructive Lung Disease stage II–IV) received tiotropium/olodaterol for 6 weeks, then tiotropium for 6 weeks, or vice versa. The primary endpoint was inspiratory capacity (IC) at peak post-dose.ResultsAdjusted mean IC after 6-week treatment was 1.990 L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 27 publications
(27 reference statements)
2
36
2
Order By: Relevance
“…35 A previous study reported a slight improvement in physical activity of more than moderate intensity following dual-bronchodilator tiotropium/olodaterol compared to mono-bronchodilator tiotropium. 11 COPD patients who participated in the SCOPE study were mostly characterized by moderate COPD with mild symptoms. Interestingly, it was predicted that physical activity with moderate to vigorous intensity would improve due to mild symptoms, and indeed, a reduction of time for physical activity at 1.0–1.5 METs was observed.…”
Section: Discussionmentioning
confidence: 99%
“…35 A previous study reported a slight improvement in physical activity of more than moderate intensity following dual-bronchodilator tiotropium/olodaterol compared to mono-bronchodilator tiotropium. 11 COPD patients who participated in the SCOPE study were mostly characterized by moderate COPD with mild symptoms. Interestingly, it was predicted that physical activity with moderate to vigorous intensity would improve due to mild symptoms, and indeed, a reduction of time for physical activity at 1.0–1.5 METs was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a postulate of downward spiral of health resulting from curative-intent therapy (E- Figure 1), efforts to improve physical exercise, function, and QoL in lung cancer survivors may need to first optimize medical therapy for cardiopulmonary disease [41] and possibly psychiatric illness [42] to alleviate dyspnea to be effective. Recent randomized controlled trials in COPD patients show that combination bronchodilator inhaler therapy is effective in reducing dyspnea [43] and possibly in improving physical activity [44,45]. Initiation of these inhalers, particularly in survivors with concomitant COPD, may be an important first step.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the values of indicators of PA can easily fluctuate based on several factors, in other words, the indicators of PA show poor reproducibility. This might be the reason why the different studies have reported inconsistent results regarding the effects of bronchodilators on PA in COPD patients [31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]. 'Physical activity' can be defined as "any bodily movement produced by skeletal muscles that results in energy expenditure" [18], but it is usually defined as physically active behavior that is comparable to moderate to vigorous-intensity PA (MVPA) [19,20].…”
Section: Sedentary Behaviormentioning
confidence: 99%
“…Among a total of 392 reports related to the effects of bronchodilators on PA in COPD patients that were registered in the PubMed database from 2005 to 2020, 15 reports that measured PA with an accelerometer were selected ( Figure 3) [31,[39][40][41][42][43][44][45][46][47][48][49][50][51][52]. Among these 15 reports, 8 studies reported that bronchodilators were effective for improving PA, 3 studies reported that some bronchodilators were suggested to be effective by some indicators but not other indicators, and 4 studies reported that bronchodilators were ineffective (Tables 2-4).…”
Section: Effectiveness In Copdmentioning
confidence: 99%
See 1 more Smart Citation